Prevalence of and factors associated with utilization of herbal medicines among outpatients in primary health centers in Cambodia - Hattie Pearson; Tyler Fleming; Pheak Chhoun; Sovannary Tuot; Carinne Brody; Siyan Yi (BMC, 2018)
Abstract Background Traditional, complementary and alternative medicine (TCAM) is seen as a way to provide healthcare in both developed and developing countries across the world. In Cambodia, there is a long tradition of using TCAM. However, scant studies have been conducted on the extent of Cambodian TCAM use and how it interacts with allopathic health care to date. In this study, we examined the prevalence of and factors associated with utilization of herbal medicines among patients with chronic diseases in primary health care settings in Cambodia. Methods A cross-sectional survey was conducted in 2015 with outpatients receiving treatment and care for chronic diseases in two urban and two rural primary health centers purposively selected from Phnom Penh, Kampong Cham and Siem Reap. Every eligible patient was randomly selected at the health centers using a systematic sampling procedure. I-CAM-Q was used to measure TCAM use. A multivariate logistic regression model was constructed to identify factors associated with herbal medicine use. Results In total, 1602 patients were included in this study, of whom 77.7% were female, and 51.2% were recruited from urban primary health centers with a mean age of 46.5 years (SD = 15.2). Of total, 27.0% reported at least one consultation with a TCAM provider in the past 12 months. The most common modality of TCAM used was herbal medicine (89%). Herbs were obtained at drug or folk stores (36.9%), from herbalists directly (28.5%) or from their own gardens (18.6%). Of herb users, 55.2% reported that herbs were somewhat helpful. After adjustment, herb users were significantly more likely to be female (AOR = 1.42, 95% CI = 1.12-2.67), have completed less schooling (AOR = 0.66, 95% CI = 0.45-0.96), were unemployed or homemakers (AOR = 0.23, 95% CI = 0.13-0.52) and have a gastrointestinal illness (AOR = 0.49, 95% CI = 0.39-0.62). Conclusions Herbal medicines are broadly used among chronic disease patients in Cambodia. Understanding TCAM use in the general population will support health care practitioners and policy makers to make informed decisions about the use of TCAM. Integration of TCAM into the primary health system should be further explored.